Dating the last Middle Palaeolithic of the Crimean Peninsula: New hydroxyproline AMS dates from the site of Kabazi II. Issue 156 (July 2021) - Spindler, Luke; Comeskey, Daniel; Chabai, Victor; Uthmeier, Thorsten; Buckley, Michael; Devièse, Thibaut; Higham, Thomas
Abstract: Radiocarbon dating of bone and charcoal from sites dating to the Middle and Upper Paleolithic is challenging due to low residual levels of radiocarbon. This means that small amounts of contaminating carbon can wield a great influence over accuracy unless they are fully removed. The site of Kabazi II in the Crimea is important because radiocarbon dates previously obtained from bones in archaeological horizons that date to the Western Crimean Mousterian (WCM) are surprisingly young. We redated the same samples using a single compound dating method that focuses on extracting and dating the amino acid hydroxyproline. We show that single amino acid dates produce significantly older determinations than those that use bulk collagen pretreatment procedures. Our results suggest that instead of dating to 35, 000–40, 000 cal BP, the bones actually date to >50, 000 cal BP. This implies that the WCM at this site is much older than previously thought. In light of these current findings, we considered the dates of other key Crimean sites and concluded that in the absence of reliable pretreatment methods, it would be wise to consider many of them minimum ages. We conclude that there is little robust evidence to suggest Neanderthals were present in the Crimea after 40, 000 cal BP.